Comparative genomic analysis of two emergent human adenovirus type 14 respiratory pathogen isolates in China reveals similar yet divergent genomes - Zhang, Qiwei (Emerg Microbes Infect, 2017)
Human adenovirus type 14 (HAdV-B14p) was originally identified as an acute respiratory disease (ARD) pathogen in The Netherlands in 1955. For approximately fifty years, few sporadic infections were observed. In 2005, HAdV-B14p1, a genomic variant, re-emerged and was associated with several large ARD outbreaks across the U.S. and, subsequently, in Canada, the U.K., Ireland, and China. This strain was associated with an unusually higher fatality rate than previously reported for both this prototype and other HAdV types in general. In China, HAdV-B14 was first observed in 2010, when two unrelated HAdV-B14-associated ARD cases were reported in Southern China (GZ01) and Northern China (BJ430), followed by three subsequent outbreaks. While comparative genomic analysis, including indel analysis, shows that the three China isolates, with whole genome data available, are similar to the de Wit prototype, all are divergent from the U.S. strain (303600; 2007). Although the genomes of strains GZ01 and BJ430 are nearly identical, as per their genome type characterization and percent identities, they are subtly divergent in their genome mutation patterns. These genomes indicate possibly two lineages of HAdV-B14 and independent introductions into China from abroad, or subsequent divergence from one; CHN2012 likely represents a separate sub-lineage. Observations of these simultaneously reported emergent strains in China add to the understanding of the circulation, epidemiology, and evolution of these HAdV pathogens, as well as provide a foundation for developing effective vaccines and public health strategies, including nationwide surveillance in anticipation of larger outbreaks with potentially higher fatality rates associated with HAdV-B14p1.